A Comparison Of Plato And Aristotle’s Ethical Thoughts - Nietlong, Joseph; Kato, Gideon (PREDESTINASI, 2020)
Many thinkers tend to glide over the differences between the ethical thoughts of Plato and his protégé Aristotle. This study is a critical discourse on whether and how Aristotle’s ethical thought seems to differ from Plato’s. Most contemporary ethicist regards both as virtue-ethicists. This is equally applicable to pre-modernist ethics. As such, ethics for the most part lays much emphasis on elements of character. However, it would seem that there are deep crevices between Plato’s and Aristotle’s ethical positions. These differences arise from fundamentally different metaphysical positions regarding the unity of being especially as adumbrated in the sixth chapter of the Nicomachean Ethics where Aristotle applies this doctrine to his Ethics. For Plato, on the other hand, all knowledge comes from knowledge of a Form, which is a universal or genus in which individuals or species share or participate. The possibility of a Philosopher King depends on the fact that there is on Form (Being as such) which encompasses everything else. Therefore, one who has knowledge of this form is in possession of the master science that subsumes all other knowledge. For Aristotle, the universality of being is not the same as that of other universals, and so cannot be the subject of a supreme science, except to show why it is not possible in the way we see in Plato’s Republic. Understanding this shows how philosophy relates to everyday life.